miRNAs regulate immune response and signaling during hepatitis C virus infection - Zhu, Huange (Eur J Med Res, 2018)
Hepatitis C is one of the most common types of viral hepatitis that impair human health. At present, there is still no effective specific therapy for hepatitis C virus infection. As host immunity is an important mechanism to defend against or clear infections, the interactions between the virus and the host immune response are crucial to the progress of the disease. Of note, hepatitis C virus infection has been reported to regulate cellular miRNAs, which play significant roles in many processes, including infection and immunity. In this review, we describe how miRNAs regulate the host immune response to hepatitis C virus via complex signaling pathways.